Muslim Businessmen and Chinese Economics in Singkawang - Fachrurazi Fachrurazi; Dwi Surya Atmaja; Zaenuddin Hudi Prasojo (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Instead of being known as the â€œCity of Tasbihâ€, nowadays Singkawang is either known as the â€œCity of Amoy (Chinese girls)â€ or the â€œCity of Thousand ChineseTemplesâ€. Cap Go Meh annually International Festival is another evidence of Chinese image making towards the city.Â This indicates a sort of Chinese domination that must be studied, economically, politically, and socially. Furthermore, the research aims to explore the dynamics of Chinese Counterpart especially the Muslim Business elites' challenge such as ironic the ongoing dominating development. To explore the dynamics, in-depth interviews were held. Key figures among Muslim businessmen, Chinese elites, government officials, even laypeople were questioned in order to obtain a clear description and balanced analysis of possible biases and perspectives of the interviewees. Quantitative data are analyzed and discussed.Â In short, the researchâ€™s findings are: The desire of an Islamic Singkawang is still intact, driven mainly by Muslim businessmen, in order to defend the existence and of Muslim in face of their powerlessness amidst the domination of Chinese elites.Keywords: Muslim; businessmen, Chinese, economics, domination, Singkawang